(untitled) (Research, Society and Development, 2021)
Fractured and darkened teeth compromise the aesthetics of the smile and can result from situations of dental trauma, which can also negatively affect the individual’s occlusion and psychosocial development. The objective of this study is to report a clinical case of replacement of class IV restoration in composite resin with the use of a silicone palatal guide on a fractured tooth with a darkened substrate. Female patient, 23 years old, sought care complaining of unsatisfactory restoration on tooth 21. It was proposed to replace the restoration and masking of the darkened substrate with direct composite resin. Molding of the upper arch and diagnostic waxing was performed to make a silicone palatal guide. The old restoration was removed; color selection of the restorative material; rubber dam isolation of the operative field; prophylaxis with pumice paste and water; conditioning with 35% phosphoric acid (30 seconds in enamel and 15 seconds in dentin); tooth washing and drying; applications two layers of universal adhesive and light curing. Sequentially, a highly translucent composite resin was inserted into the palatal guide, taken in the mouth, to make the palatal shell; construction of the opaque dentin body; contour definition and characterization with resin for enamel, followed by finishing and polishing. The treatment employed proved to be effective for returning the shape and color compatible with the adjacent teeth. The use of the silicone guide allowed good levels of marginal adaptation and facilitated the step of increasing the restorative material.